The anti-derivative of a function f(x) is another function F(x) so that F´(x) = f(x).
If f(x) = x^n (n<-1 or n>-1) then the anti-derivative is F(x) = (x^(n+1))/(n+1) + C ... we need to add an arbitrary constant.
In your case we have: f(x) = x^1 and F(x) = (x^2)/2 + C
2006-11-30 08:57:39
·
answer #1
·
answered by vahucel 6
·
1⤊
1⤋
Just add one to the exponent and then divide by that number.
The antiderivative of x^1 is x^(1+1) / (1+1) + C
= x^2 / 2 + C
= (1/2)x^2 + C
2006-11-30 16:45:46
·
answer #2
·
answered by MsMath 7
·
0⤊
1⤋
the antiderivative of x^p = [x^(p+1)] / (p+1)
2006-11-30 16:47:30
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
(1/2)x^2
2006-11-30 16:46:55
·
answer #4
·
answered by Josh H 2
·
0⤊
1⤋
(1/2)x^2
2006-11-30 16:46:26
·
answer #5
·
answered by Herb J 2
·
0⤊
1⤋
Add one to the exponent and then divide by that number.
(1/2)x^2
2006-11-30 16:47:07
·
answer #6
·
answered by barnacle1988 3
·
0⤊
0⤋
Y
I mean why do you want to know
2006-11-30 16:47:18
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋